American Welding Society And Bureau Of Welding (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1919)
In opening the meeting I wish to express my greatest pleasure at being able to greet this joint session of the Mining and Electrical Engineers. As engineering develops, we find that the border lines between the different branches of engineering become more and more indistinct; the several fields overlap so much that they are three or four layers deep in places. It is only an accident that we couldn't have had the Mechanical Engineers also as a formal part of this gathering, because they are quite as much interested in this subject as the Electrical or Mining Engineers. A little history may enlighten some of those who have not been close to this work. A year ago last summer, there was brought to the attention